Analisis Proksimat dan Serat Pangan pada Pembuatan Snack Bar dengan Penambahan Kesemek (Diospyros kaki L.) dan Kacang Koro Pedang (Canavalia ensiformis [L.] DC) - Hasna Fairuz Fadhoil; Kurniati, Wenny Dwi; Hayati, Nur (Media Gizi Ilmiah Indonesia, 2024)
An unbalanced diet results in adolescents having more nutritional status. Adequate intake of nutrients and fiber is needed to meet balanced nutrition. One of them is by diversifying food products in the form of snack bars that utilize local plants, namely persimmons and sword beans. The purpose of this study was to determine the organoleptic properties, nutritional content, and dietary fiber of snack bars with the addition of persimmons and sword beans. This study was an experimental study with five treatments and three repetitions. All samples were proximate tested while food fiber test used the best formulation (F2) and control. Organoleptic tests showed no noticeable differences (p>0.05) in color and texture and showed no noticeable differences (p<0.05) in taste, aroma, and acceptability. The laboratory test results showed an increase in ash, protein, and fat content parameters while the water and carbohydrate content parameters showed a decrease. Based on organoleptic test results, the F2 (50:50) formulation is the panelist’s most preferred formulation with a moisture content of 3.73%; ash content 2.67%; fat content 26%; protein content 16,19%; carbohydrate content of 53.70%; and dietary fiber by 12.65%.